Performance Degradation Predictions Based on Microstructural Evolution Due to Grain Coarsening Effects in Solid Oxide Fuel Cell Electrodes. Issue 2 (17th January 2018) - Mason, Jerry; Celik, Ismail; Lee, Shiwoo; Abernathy, Harry; Hackett, Gregory
Abstract : Due to the time required to test fuel cell degradation experimentally, a physics-based model which can predict degradation can be a valuable tool. Grain coarsening and the resulting microstructure evolution is a primary mode of degradation. In this study, a multi-physics model of a fuel cell is presented which can predict performance loss as a function of time caused by coarsening in the electrodes of an LSM-YSZ/YSZ/Ni-YSZ SOFC. Microstructural properties are updated as a function of time from their initial values using functional relations derived from experimental data. Specie and charge transport equations are solved to predict performance changes with time from the microstructural changes. The model is first calibrated such that it correctly captures the performance of a button cell. Performance change over time predicted by the model is compared to experimental data for a cell operated for 775 hours. It is found that the model predicts a slower degradation rate than the rate which occurs experimentally. This is reasonable as other forms of degradation are not being accounted for. The model is then used to make long term predictions of cell performance loss due to grain coarsening out to 40, 000 hours for various operating temperatures and initial microstructures.